Pneumocephalus as a complication after bilateral chronic subdural hematoma evacuation. - Jakub Litak; Agnieszka Budny; Joanna Litak; Wojciech Czyżewski; Cezary Grochowski (Kazimierz Wielki University, 2017)
Pneumocephalus (PNC) is described as a presence of air in the cranial cavity. Trauma is the most common cause, other etiologies such as iatrogenic. There are  two main  types of pneumocephalus: simple and tension. Simple one is typically non- symptomatic and requires no treatment. Tension Pneumocephalus is an acute state when a valve mechanism allows air to enter the scull cavity but prevent it form escaping outside. Presented case reveal Simple Pneumocephalus which developed after both sided CSDH(chronic subdural hematoma) treated with bilateral burr -holes operation. Despite great amount of air intracranially Patient did not develop  neurological deficits.